The Influence of Liquidity and Solvability on the Bond Ratings of Indonesia stock exchange : Evidence From the Raw Materials Sector - Rifma Istifariana; Sumilir Sumilir; Yudi Nur Supriadi (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
Bonds are issued by companies and government agencies seeking capital with long-term debt. Bonds still carry risks for investors, namely the possibility of default, like other financial assets . Bond ratings are one indicator that can be used to measure this risk. Liquidity and sovability ratios can be used as indicators that can assess a company's capacity to pay all short and long term debts on time. The aim of this research is to examine the influence of liquidity ratios and solvency ratios on the bond ratings of basic materials sector companies listed on the Indonesia Stock Exchange. The objects of observation in this research are all public companies in the basic materials sector which are listed on the Indonesia Stock Exchange and whose bonds are rated by PT. Pefindo during the 2017-2021 period. Observations were taken using a purposive sampling technique because they have certain criteria. The method used in this research uses panel data regression analysis techniques with the help of E-Views 12. The research results show that 1) liquidity can be used as a benchmark to influence the rating of a bond and 2) the solvency ratio cannot be used as a benchmark that can influence the rating of a bond. Key words: bonds; bond ratings; liquidity ratio; solvency ratio; cash ratio; debt to equity ratio